2022
DOI: 10.3390/healthcare10020258
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome among Staff at an Emergency Department during the COVID-19 Pandemic

Abstract: Objective: The aim of this current study was to identify the prevalence of burnout manifestation in a sample recruited from the emergency department of a hospital. Moreover, we aimed to assess the role of professional experience, age, and the professional category in shaping burnout manifestations. Results: The results showed that higher proportions of burnout symptoms were reported by resident physicians, nurses, and physicians whereas lower proportions were encountered in the orderly group. Moreover, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
2
8
0
1
Order By: Relevance
“…Our survey shows that females have a higher level of overall burnout compared with males, with statistical significance, although with a reduced effect (OR 1.2). The same results are confirmed by other publications [ 42 ], and the absence of interaction of gender with profession or working place suggests an independent gender effect.…”
Section: Discussionsupporting
confidence: 91%
“…Our survey shows that females have a higher level of overall burnout compared with males, with statistical significance, although with a reduced effect (OR 1.2). The same results are confirmed by other publications [ 42 ], and the absence of interaction of gender with profession or working place suggests an independent gender effect.…”
Section: Discussionsupporting
confidence: 91%
“…Concerning the differences between different professional categories, the results showed that trainees presented higher scores for worries, perceived threats, and anxiety symptoms, as well as lower scores for general health. In a previous study conducted with Romanian physicians from Emergency Care staff [ 19 ], trainees or senior house officers represent the professional category with a high probability of developing burnout manifestations. These results are in line with the fact that, in the present study, more years of professional experience were associated with low anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical results from studies conducted with nurses and physicians from the emergency departments documented the presence of peritraumatic distress, burnout, anxiety, depression, somatic symptoms, and posttraumatic stress reactions (e.g., intrusions, hyper-arousal) [ 2 , 19 ]. Even if all these professionals are able to use their abilities in order to save lives, they may develop long-term negative psychological traumatic manifestations [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic lung diseases and COVID-19 are leading causes of disease, death and disability globally 1 4 which entail a substantial burden on the individual 5 7 and healthcare systems. 8 , 9 Pulmonary rehabilitation (PR) is defined by the “National Heart, Lung, And Blood Institute” as a “supervised program that includes exercise training, health education, and breathing techniques for people who have certain lung conditions or lung problems due to other conditions” 10 is widely recognized as an important treatment for patients suffering from chronic respiratory diseases, 11 , 12 and has been recommended as a potential beneficial intervention for post-COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%